You gotta believe [videorecording (DVD)] - Garrison, Lane, 1980-; Wilson, Luke, 1971-; Kinnear, Greg, 1963-; Gadon, Sarah, 1987-; Kellici, Etienne; Fry, Nicholas, 2008-; Temple, Lew; Roach, Martin, 1962-; Cash, Michael (Actor); Renna, Patrick, 1979-; Parker, Molly, 1972-; Cameron, Stuart James; et al. (Well Go USA Entertainment, 2024)
Based on the inspirational true story, an underdog youth baseball team of misfits come together and dedicate their season to a player's dying father. In doing so, they defy all odds and accomplish the impossible by reaching the Little League World Series in an unforgettable game now considered an ESPN and LLWS classic.